Kebijakan pinjaman kebajikan menggunakan Al-qardh Baitul Maal wat Tamwil - Fajar, Osama Malik (Maliki Interdisciplinary Journal, 2024)
The main focus of this research is the public financial administration of Baitul Maal wat Tamwil on managing Al-Qardh funds, and maximizing BMT funds, especially at Al-Qardh. This study combines research and learning. The method used is the Information method used in this research comes from different sources: BMT financial reports provide secondary information, producing basic information. data collection through studies and descriptive analysis techniques. This research shows that managing Al-Qardh funds at BMT provides benefits for underprivileged communities in running a business. BMT needs to be developed, especially because Indonesia is predominantly Muslim.